Expanding the functional role of long noncoding RNAs - Johnsson, Per (Cell Res, 2014)
New findings bring to light a previously unappreciated mechanism involved in the regulation of the oncoprotein MYC. Interesting observations find that the long noncoding RNA (lncRNA) PVT1 is active in controlling levels of MYC through regulation of MYC protein stability.